3.2x-9.6=-.4x+1.2
3.2x=-.4x+10.8
3.6x=10.8
X= 3
Answer:
No solutions.
Step-by-step explanation:
5x = 8x^-1/3
Divide 8 into both sides.
5/8x = x^-1/3
Divide both sides by x.
5/8 = x^-4/3
Multiply both sides by the exponent -3/4.
5/8^-3/4 = x
1.422624 = x
Plug in 1.422624 for x to check.
It does not work. There are no real solutions.
Answer:
26
hope this heps and pls mark brainliest :))
Step-by-step explanation:
Answer:
Jenny is wrong the correct answer is x²+ 4 - 4 x.
Step-by-step explanation:
Given that
(x-2)³∕x-2
(x-2)³∕(x-2) =(x-2) (x-2)²∕(x-2)
(x-2)³∕(x-2) = (x-2)²
As we know that
(a-b)² = a²+b² - 2 ab
So
(x-2)² = x²+ 2² - 2 ˣ 2 ˣ x = x²+ 4 - 4 x
(x-2)² = x²+ 4 - 4 x
It means that
(x-2)³∕(x-2) = (x-2)² = x²+ 4 - 4 x
So Jenny is wrong the correct answer is x²+ 4 - 4 x.